2008
DOI: 10.1159/000167273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ATP-Induced Local and Conducted Vasomotor Responses in Isolated Rat Cerebral Penetrating Arterioles

Abstract: Background: Adenosine triphosphate (ATP), a potent vascular regulator in the cerebral circulation, initiates conducted vasomotor responses which may be impaired after pathological insults. We analyzed the mechanism of ATP-induced local vasomotor responses and their effect on conducted vasomotor responses in rat cerebral penetrating arterioles. Methods: Arterioles were cannulated and their internal diameter monitored. Vasomotor responses to ATP were observed in the presence or absence of inhibitors, or after en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 42 publications
(76 reference statements)
8
71
1
Order By: Relevance
“…The local EC Ca 2 þ increase will cause hyperpolarization and secondary local dilatation by activating endothelial IK Ca channels directly, 36,58 and indirectly activating VSMC BK Ca channels through a PLA 2 /CYP450/ EET-dependent mechanism. 74,75 The conducted dilatations to local ATP were dependent on an intact endothelium and were preceded by conducted hyperpolarization, 73 consistent with electrotonic conduction and electromechanical coupling of the conducted vasomotor responses as observed in other systemic arterioles. 15,27,32 Nitric oxide synthase or cyclooxygenase inhibition did not affect the conducted vasodilatation.…”
Section: Vascular Conducted Responses In the Cerebral Microcirculationsupporting
confidence: 74%
See 1 more Smart Citation
“…The local EC Ca 2 þ increase will cause hyperpolarization and secondary local dilatation by activating endothelial IK Ca channels directly, 36,58 and indirectly activating VSMC BK Ca channels through a PLA 2 /CYP450/ EET-dependent mechanism. 74,75 The conducted dilatations to local ATP were dependent on an intact endothelium and were preceded by conducted hyperpolarization, 73 consistent with electrotonic conduction and electromechanical coupling of the conducted vasomotor responses as observed in other systemic arterioles. 15,27,32 Nitric oxide synthase or cyclooxygenase inhibition did not affect the conducted vasodilatation.…”
Section: Vascular Conducted Responses In the Cerebral Microcirculationsupporting
confidence: 74%
“…71 ATP and ADP caused initial local vasoconstriction followed by a secondary local vasodilatation, which was conducted rapidly and in a decaying manner to remote sites. [71][72][73] The local constriction to ATP was inhibited by low concentration of pyridoxalphosphate-6-azophenyl-2 0 ,4 0 -disulfonic acid (3 mM) and a,b-methylene ATP (1 mM), showing that P2X-receptors are involved. 73 The local secondary dilatation was reduced by impairment of endothelial function using air emboli, while the local constriction was enhanced by this procedure.…”
Section: Vascular Conducted Responses In the Cerebral Microcirculationmentioning
confidence: 95%
“…ATP and ADP relaxation of monkey temporal and cerebral arteries was endothelium dependent in temporal arteries, but largely endothelium independent in cerebral arteries (Toda et al, 1991). In rat cerebral arterioles in vivo, microapplication of ATP produced a biphasic response consisting of a transient constriction via smooth muscle P2X 1 receptors and a subsequent dilation primarily due to endothelial P2Y receptor activation (Dietrich et al, 2009). It was shown further that conducted vasomotor responses travel along the vessel with a membrane hyperpolarization that precedes vessel dilation (Dietrich et al, 2009).…”
Section: F Cerebral Vesselsmentioning
confidence: 98%
“…In rat cerebral arterioles in vivo, microapplication of ATP produced a biphasic response consisting of a transient constriction via smooth muscle P2X 1 receptors and a subsequent dilation primarily due to endothelial P2Y receptor activation (Dietrich et al, 2009). It was shown further that conducted vasomotor responses travel along the vessel with a membrane hyperpolarization that precedes vessel dilation (Dietrich et al, 2009). It has been suggested that in female rat pial arterioles, ADP-induced dilation is the result of additive contributions from P2Y 1 receptors present on endothelium but also on the glia limitans, the underlying layer of astrocytic glial processes (Xu et al, 2005).…”
Section: F Cerebral Vesselsmentioning
confidence: 99%
“…Transient withdrawal of glucose, the major energy substrate for neurons, as well as removal of amino acids from the culture medium results in mitochondrial depolarization, reduced ATP production, and the development of delayed tolerance against various insults, such as OGD, glutamate excitotoxicity, and exogenous hydrogen peroxide (63). Breakdown products of ATP: adenosine, AMP, ADP, as well as ATP itself, are vasoactive stimuli in cerebral arteries (36,123).…”
Section: Role Of Mitochondria In Cellular Protectionmentioning
confidence: 99%